THE KINETIC APPROACH OF LATERAL EPICONDYLITIS RECOVERY - M. DAN; A. PRALĂ (Editura Universitatii Transilvania din Brasov, 2018)
We conducted a study of 10 patiets affected by lateral epicondylitis, 5 woman and 5 men, aged between 20 and 38. In the initial evaluation, I applied 2 tests: VAS Scale, for pain assessment and Oxford Questionnaire to assess the functional deficit. Initial testing showed a very high value of the pain scale, an average of 8,5 out of 10 and the Oxford questionnaire demonstrated that the deficiencies caused by epicondylitis make the usual activities very difficult, as evidenced by an average of 21,3 out of 48. After 20 days of the rehabilitation treatment, meanwhile I worked on improvingin the analgesia andrestoring mobility and stability within the functional limits, I obtained a final assessment of the improvement of Pain Scale and Oxford Questionnaire scores.